Effect of Debt Structure on Earnings Quality of Energy Businesses in Vietnam - Phuong, Nguyen Thi Thanh; Hung, Dang Ngoc; Van, Vu Thi Thuy; Xuan, Ngo Thanh (International Journal of Energy Economics and Policy, 2020)
The paper examines the impact of debt structure (DS) on the earnings quality (EQ) of energy businesses (DN) in Vietnam. The authors measure EQ in terms of profit management to consider the effect of accounts payable; short-term debts and loans; long-term debts and loans on earnings quality. The research uses generalized least squares (GLS) regression method with data gathered from 468 observations collected at energy enterprises listed on the stock market in Vietnam in the period of 2009-2018. The study results have found that accounts payable to suppliers and short-term debts and loans have negative effect on earnings quality; while long-term debts and loans have positive effect on EQ. Besides, firm size has a positive effect on EQ, while profitability is a not statistically significant variable. The empirical research results are useful basis to help businesses improve their earnings quality, thereby helping businesses to consider an appropriate level of debt structure. Keywords: debt structure; earnings quality, energy business JEL Classifications: M40, G32, Q43 DOI: https://doi.org/10.32479/ijeep.9110